Kidney damage from nonsteroidal anti‐inflammatory drugs-Myth or truth? Review of selected literature - Sylwester Drożdżal; Kacper Lechowicz; Bartosz Szostak; Jakub Rosik; Katarzyna Kotfis; Anna Machoy‐Mokrzyńska; Monika Białecka; Kazimierz Ciechanowski; Barbara Gawrońska‐Szklarz (Wiley, 2021)
Abstract Nonsteroidal anti‐inflammatory drugs (NSAIDs) are widely available drugs with anti‐inflammatory and analgesic properties. Their mechanism of action is associated with the enzymes of the arachidonic acid cycle (cyclooxygenases: COX‐1 and COX‐2). The cyclooxygenase pathway results in the formation of prostanoids (prostaglandins [PGs], prostacyclins, and thromboxanes). It affects various structures of the human body, including the kidneys. Medical literature associates the usage of NSAIDs with acute kidney injury (AKI), tubulointerstitial nephritis (TIN), as well as nephrotic syndrome and chronic kidney disease (CKD). AKI associated with the chronic consumption of NSAIDs is mainly attributed to pharmacological polytherapy and the presence of cardiovascular or hepatic comorbidities. The pathomechanism of AKI and CKD is associated with inhibition of the biosynthesis of prostanoids involved in the maintenance of renal blood flow, especially PGE2 and PGI2. It is suggested that both COX isoforms play opposing roles in renal function, with natriuresis increased by COX‐1 inhibition followed by a drop in a blood pressure, whereas COX‐2 inhibition increases blood pressure and promotes sodium retention. TIN after NSAID use is potentially associated with glomerular basement membrane damage, reduction in pore size, and podocyte density. Therefore, nephrotic proteinuria and impairment of renal function may occur. The following article analyzes the association of NSAIDs with kidney disease based on available medical literature.